Operations Management in the Era of Fast Fashion Technologies and Circular Supply Chains - Chan, Hau-Ling; Ren, Shuyun; Liu, Na (Springer Series in Fashion Business, 2022)
IX, 141 p. 22 illus., 12 illus. in color.